Regulação emocional e competências sociais em crianças e jovens institucionalizadas - Pinto, Tânia (2022)
Risk situations in childhood and youth are often characterized by the failure in meeting physical and socio-emotional needs with an impact on children and young people development. Institutionalization emerges as a measure of promotion and protection, with a fundamental role in promoting emotional regulation and the development of social skills. This quantitative, non-experimental and exploratory study aimed to assess the quality of emotional regulation and the mastery of social skills in institutionalized children and young people. The sample was selected by convenience and included 24 participants, between 10 and 21 years old (15.63±2.20), institutionalized in a residential care home for female children and young people. Two age groups were organized (cutoff point 16 years) for comparisons to be made. Most attended the 2nd cycle (50%) and secondary (41.7%). They completed the Portuguese version of the Emotion Regulation Index for Children and Adolescents (ERICA). The Social Skills Assessment Questionnaire was completed by professionals who accompanied the 24 children and youth. In the data analysis, SPSS – IBM 27 was used, with a confidence level of 95% in the interpretation of the non-parametric tests used. In general, children/young people showed an adaptive emotional regulation, albeit with moderate values (3.20±0.52) according to the instrument scale from 1 to 5. The Emotional Control subscale (2.96±0.68) stood out on the negative side, and the Emotional Responsibility subscale (3.93±0.79) on the positive side, as it was close to a high level. With regard to social interaction skills, from the perspective of the professionals, children/young people showed a moderate level of social competence (3.09±0.33), on a scale from 1 to 5, with better results in Conversation Skills (3.29 ±0.34). In turn, the Problem Solving and Basic Social Skills subscales were negative (2.78 ±0.46 and 2.88 ±0.42, respectively). There were no age differences or differences in terms of education level, in emotional regulation and social skills. In the latter, the Assertiveness subscale showed statistically significant differences (p=.04) as a function of age, favorable to the older ones. Emotional regulation was positively correlated with social skills (rs=.48, p=.015) and respective subscales of Assertiveness (rs=.49, p=.013) and Conversation Skills (rs=.53 p= .007); this, in turn, correlated with the dimensions of the emotional regulation scale, Emotional Control (rs=.42, p=.041) and Emotional Self-Awareness (rs=.47, p=.021). The attention and adoption of promoting and restorative strategies in terms of socio-emotional development must be assumed as a central concern, alongside the guarantee of basic care needs, by the professionals of these institutions, especially concerning the less developed skills we found in our study. Boosting the emotional regulation of these children and young people at risk will have effects on the development of essential social skills for future adult life in society, breaking with dysfunctional patterns of relationships that often characterize the early experiences of this population.